A study on rate pressure product in south Indian pregnant women with anaemia - Venugopal, Lalitha; Rajendran, Priyadharsini; V., Parghavi (International Journal of Advances in Medicine, 2018)
Background: Anaemia is a cause of serious concern and contributes to a significantly higher maternal mortality. Rate Pressure Product (RPP) is a major determinant of myocardial oxygen consumption and blood flow. There is an increase in oxygen demand in anemia. Thus, in the present study, we have compared the difference in RPP between a normal pregnant women and pregnant women with anemia. Methods: A total of 180 pregnant women (normal pregnant woman - 90 and pregnant woman with anaemia - 90) belonging to different trimesters of pregnancy were included in the study. Age, height, and weight were recorded, and their body mass index was calculated. The systolic blood pressure, diastolic blood pressure, heart rate was recorded and RPP was calculated. Results: There was a significant increase in RPP in pregnant woman with anaemia in all three trimesters of pregnancy, but the significant increase was more in the third trimester. Conclusions: The present study shows that there is an increase in RPP in pregnant woman with anaemia and they are more prone to hemodynamic stress and cardiovascular risks, especially in their third trimester of pregnancy. This hemodynamic change may be taken into account to prevent the cardiovascular complications associated with anemia in pregnancy. Thus, RPP can be used as a sensitive non-invasive simple marker for early diagnosis of cardiovascular disease in pregnant woman.